The Exploration of Factors Influencing Service Quality for Café Visitors in Bandung City - Imelda Megawati; Retno Resawati; Erisca Marcella (Majalah Bisnis & IPTEK, 2025)
The creative economy, particularly in the tourism sector, plays a vital role in strengthening regional economies, with cafés and restaurants being essential components of this ecosystem. This study aims to explore the factors influencing service quality for café visitors in Bandung, as the culinary sector significantly impacts the city's economy. Utilizing a survey approach, data will be collected from a sample of 300 café and restaurant visitors affiliated with the Indonesian Hotel and Restaurant Association (PHRI) in Bandung. The research will employ Exploratory Factor Analysis (EFA) to identify key dimensions of service quality. The expected outcome is to enhance service quality in cafés and restaurants, ultimately improving customer satisfaction. This research addresses the urgent need for specific indicators related to service quality in the café industry, contributing valuable insights for stakeholders to optimize their service offerings.